A quest for modernity: reorienting the state-peasant relation, dilemmas and ramifications in northwestern Ethiopia, 1941–1974 - Dejenie Fikremaryam; Tekalign Woldemariam (Cogent Arts & Humanities)
The Horn of Africa witnessed a remarkable shift during the latter half of the 19th century. In the face of colonial powers’ mounting influence, Ethiopian rulers took decisive action to protect their country’s territorial integrity and sovereignty. Their response involved embracing Western-style modernity, aiming to overhaul the traditional Gult-based mode of governance with a modern, centralized administrative system. However, the lack of credible works documenting the implementation of this project at the local level has left a significant gap in our understanding. Therefore, our paper aims to rectify this shortcoming by providing a detailed, unambiguous account of the strategies employed, challenges faced, and consequences underlying this transformative project. The study underscores the indispensable nature of reorienting the longstanding state-peasant relationship for the project’s success. It also illuminates how successive administrative and land tax reforms dismantled the intermediary role of the feudal class and consolidated state power. Overall, by showcasing the diverse responses of Africans to the European threat, our research offers invaluable insights into a pivotal chapter of African history.